A Comparative Anatomical Study Of Phana Marma In Ayurveda And Modern Sinus Anatomy With Special Reference To Dushta Pratishyaya (CHRONIC RHINOSINUSITIS) - Mishra, Vikas; Gupta, Shyam Sundar (Journal of Neonatal Surgery, 2025)
Background: The disease Dushta Pratishyaya is a chronic nasal condition affecting the nasal cavity and paranasal sinuses. In contemporary medicine, it correlates with chronic rhinosinusitis. According to Ayurvedic texts, Phana Marma, classified under Vaikalyakara Marma, is situated on either side of the nostrils and is associated with the Ghrana Sangyavaha Srotas. It plays a vital role in olfactory function. Olfactory loss may be partial (hyposmia) or complete (anosmia), & its duration depends on the underlying pathology. Materials and Methods: This anatomical study of Phana Marma draws references from the Brihattrayi, Laghutrayi, and other classical Ayurvedic sources, supported by modern anatomical and clinical literature including journals, dissertations, and conference papers. The study included 31 patients who presented with symptoms such as rhinorrhea, nasal blockage, headache, and facial pain, unresponsive to medical treatment, with radiological findings of haziness, opacification, or air-fluid levels on 45° Water’s view X-ray of the paranasal sinuses. Patients with nasal tumors, polyps, allergic mucosal thickening, previous nasal surgeries, age below 18 or above 60. Results: Out of 31 enrolled patients, 30 completed the study and were analyzed. A significant association was observed between the number of symptoms of Dushta Pratishyaya involving Phana Marma and the severity of mucosal thickening. As the number of symptoms increased, mucosal thickening progressed from mild to severe, with a statistically significant p-value (<0.05). Conclusion: This study highlights the anatomical importance of Phana Marma by establishing its correlation with the olfactory epithelium, which is located in the upper third of the nasal cavity. The olfactory axons pass through the cribriform plate and connect receptors to the olfactory bulb. Any trauma or pathology affecting these structures can result in olfactory dysfunction. The findings affirm the Ayurvedic concept of Phana Marma and its practical correlation with modern sinus anatomy and clinical manifestations of Dushta Pratishyaya.